2004
DOI: 10.1007/s00520-003-0533-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intrapericardial cisplatin administration in cases with recurrent malignant pericardial effusion and cardiac tamponade

Abstract: Cisplatin administered directly into the pericardial space is a very effective and relatively safe method of treatment of recurrent malignant pericardial effusion, especially in the course of NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Improvement of local disease control and prevention of PF recurrence may be achieved by intrapericardial instillation of cytotoxic agents such as cisplatin, thiotepa, bleomycin [8,9,[13][14][15][16]. Recently, intrapericardial activity of anti--angiogenic factor -bevacizumab was reported in NPE [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvement of local disease control and prevention of PF recurrence may be achieved by intrapericardial instillation of cytotoxic agents such as cisplatin, thiotepa, bleomycin [8,9,[13][14][15][16]. Recently, intrapericardial activity of anti--angiogenic factor -bevacizumab was reported in NPE [17].…”
Section: Discussionmentioning
confidence: 99%
“…Intrapericardial treatment tailored to the type of the tumor indicate that administration of cisplatin has been most efficient in NPE due to lung cancer [8,9,13], and intrapericardial instillation of thiotepa has been more effective in NPE due to breast cancer [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthracyclines at standard doses can induce both acute and delayed AF, with the type of AF being predominantly persistent ( Ando et al, 2000 ; Kilickap et al, 2007 ; Guglin et al, 2009 ; Amioka et al, 2016 ). Cisplatin, when administered intravenously, intrapericardial, or intrathoracically, can cause acute AF in 10%–32% of patients ( Tomkowski and Filipecki, 1997 ; Tomkowski et al, 2004 ; Bischiniotis et al, 2005 ; Lara et al, 2005 ; Richards et al, 2006 ; Tilleman et al, 2009 ; Zellos et al, 2009 ). A systematic review showed that standard doses of gemcitabine, immune checkpoint inhibitors, Marfan, abiraterone acetate, and rituximab can increase the incidence of atrial fibrillation in elderly patients, those with reduced renal function, or those with hypertension ( Olivieri et al, 1998 ; Phillips et al, 2004 ; Mileshkin et al, 2005 ; Feliz et al, 2011 ; Passalia et al, 2013 ; Sharma et al, 2017 ; Hilmi et al, 2020 ; Mascolo et al, 2023 ).…”
Section: Types Of Arrhythmias Caused By Chemotherapy Drugsmentioning
confidence: 99%
“…Among patients with adenocarcinoma of the lung and pericardial tamponade who received cisplatin perfusion, 19% showed AF (Tomkowski et al, 2004 ; Richards et al, 2006 ; Tilleman et al, 2009 ; Zellos et al, 2009 ). In a recent clinic trial, carboplatin combination therapy induced AF in one of 32 patients (Illiano et al, 2000 ).…”
Section: Anticancer Drugsmentioning
confidence: 99%